(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
In article theoretical aspects of development of the production account and classification of expenses are considered. Value of the account and formation of costs of production of finished goods in the extracting branch reveals. Optimization of profits requires constant analysis not only of external factors such as price, demand, market conditions, and internal – the formation of the cost of production and profitability. A significant share of the total expenditures occupy the cost of production and sale of goods (works, services), which consists of its cost, which is one of the key performance indicators that determine the quality of the enterprises. In modern conditions, the organization carried out in the ever-changing factors external and internal environment . External factors associated with the process of globalization of markets , increasing competition , on the one hand, and changes in demand , the development of consumer protection , the emergence of the problem of the ecological balance , on the other hand, demanded a fundamentally new methods and approaches to the management of economic activities and accounting system